2016
DOI: 10.3233/bmr-160698
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of meniscus tears in lateral tibial plateau fractures and repair results

Abstract: For successful outcomes in lateral plateau fractures, it is essential to determine whether there is a meniscus tear. In cases with meniscus tears, meniscus repair can be easily performed and should be considered because it has a positive impact on the treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Through literature review, the advantages of the extended anterolateral approach are as follows: the patient can be in the supine position; exposure of the lateral, posterior, and platform surface of the tibia is relatively clear, and sufficient operation space exists; neurovascular injury and fibular head osteotomy are avoided, and damage to the original anatomical structure is small; in anterolateral column and posterolateral column fractures, this approach can be used alone for fracture reduction and plate fixation; the learning curve is relatively simple compared with that of the posterior approach. [ 20 , 21 ] Previous studies using the extended anterolateral approach to treat posterolateral tibial plateau column fractures have achieved good clinical results. Chen et al, [ 22 ] in the last follow-up of 10 patients, revealed an average HHS score of 95.3 ± 6.5 points (range: 80–100 points), an average knee flexion of 119.8 ± 17.2° (range: 95°–140°) and an average knee extension of 2.1 ± 2.1° (range: 0°–6°).…”
Section: Discussionmentioning
confidence: 99%
“…Through literature review, the advantages of the extended anterolateral approach are as follows: the patient can be in the supine position; exposure of the lateral, posterior, and platform surface of the tibia is relatively clear, and sufficient operation space exists; neurovascular injury and fibular head osteotomy are avoided, and damage to the original anatomical structure is small; in anterolateral column and posterolateral column fractures, this approach can be used alone for fracture reduction and plate fixation; the learning curve is relatively simple compared with that of the posterior approach. [ 20 , 21 ] Previous studies using the extended anterolateral approach to treat posterolateral tibial plateau column fractures have achieved good clinical results. Chen et al, [ 22 ] in the last follow-up of 10 patients, revealed an average HHS score of 95.3 ± 6.5 points (range: 80–100 points), an average knee flexion of 119.8 ± 17.2° (range: 95°–140°) and an average knee extension of 2.1 ± 2.1° (range: 0°–6°).…”
Section: Discussionmentioning
confidence: 99%
“…nevertheless, it is di cult to expose and x the posterior tibial plateau through traditional anterolateral approach. Through literature review, the advantages of the extended anterolateral approach are as follows: the patient can be in the supine position; the exposure of the lateral, posterior and platform surface of the tibia is relatively clear, and there is enough operation space; the neurovascular injury and bular head osteotomy are avoided to a large extent, and the damage to the original anatomical structure is small; In anterolateral column and posterolateral column fractures, this approach can be used alone for fracture reduction and plate xation; the learning curve is relatively simple compared with the posterior approach [18,19]. Previous studies through the extended anterolateral approach for the treatment of posterolateral tibial plateau column fractures have achieved good clinical results.…”
Section: Discussionmentioning
confidence: 99%
“…Lateral meniscus injuries have a dramatic impact on the risk of an osteoarthritis of the knee and are often undiagnosed and nonaddressed. 30,31 A major advantage of the described method would therefore certainly be the simultaneous easy treatment of a potential meniscus pathology during further preparation. A proper indication for a central subluxation of the lateral meniscus are intra-articular comminuted tibial plateau fractures with central and/or dorsal fracture lines involving the lateral tibial plateau, especially affecting the posterolaterolateral and/or the posterolaterocentral segment, with not sufficient visualization despite submeniscal approach.…”
Section: Discussionmentioning
confidence: 99%